AM1* parameters for bromine and iodine - Kayi, Hakan; Clark, Timothy (Journal of Molecular Modeling, 2009)
Our extension of the AM1 semiempirical molecular orbital technique, AM1*, has been parameterized for the elements Br and I. The basis sets for both halogens contain a set of d-orbitals as polarization functions. AM1* performs as well as other MNDO-like methods that use dorbitals in the basis, and better than those that rely on an sp-basis. Thus, AM1* parameters are now available for H, C, N, O and F (which use the original AM1 parameters), Al, Si, P, S, Cl, Ti, Cu, Zn, Br, Zr, Mo and I.